Menjinakkan Barat Dengan Oksidentalisme: Gagasan Kiri Islam Hassan Hanafî - Suharti Suharti (Universitas Islam Negeri Mataram, 2005)
In the scholarly thoughts, some recognized Muslim scholars are among them: Nashr Hamîd Abû Zayd, Zia Ghokap, Muhammad Syahrûr, Amina Wadûd, and Hassan Hanafî. They were known for their brilliant ideas and theories in perceiving problems and finding ways out of the problems related either to Islamic affairs and the Muslims or even for the welfare of the whole humankind. The ideas that they offered through writings become inspirations and triggers to Islamic development to compete with the West. It is relative to consider one’s idea as extraordinary or ordinary. In this case, Hassan Hanafi, as one of Muslim scholars, tried to offer an idea popularly known as “al-Yasâr al-Islâmî” or “Islamic Left”. The idea proposed in the “Islamic Left” is an effort to bring back Islam and the Muslims to the previous golden era by eliminating every threat to Islam. This revolution is based on three main considerations: revitalization of classical literature, reality of Islamic world and the needs to fight against western civilization. This article is intended to trace the path of the existence of “Islamic Left” developed by Hassan Hanafî from historical background, terminology, school of thoughts, and Hassan Hanafî’s way of thinking.